2001
DOI: 10.1002/1521-3765(20010216)7:4<894::aid-chem894>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent and Electroactive Cyclic Assemblies from Perylene Tetracarboxylic Acid Bisimide Ligands and Metal Phosphane Triflates

Abstract: Tetraaryloxy-substituted perylene tetracarboxylic acid bisimides with one or two 4-pyridyl receptor substituents at the imide functionality were synthesized and employed in transition metal directed self-assembly with Pd(II) and Pt(II) phosphane triflates. Upon mixing of the components, quantitative formation of functional molecular square-type complexes containing four dye molecules and model complexes of a 2:1 (perylene bisimide ligand:transition metal ion) stoichiometry was observed. The isolated metallosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…The synthesis of pyridyl-substituted perylene bisimide (PP) and dialkyl-substituted perylene bisimide (DAP) investigated in the present experiments is described elsewhere [18,19]. PP and DAP molecules are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of pyridyl-substituted perylene bisimide (PP) and dialkyl-substituted perylene bisimide (DAP) investigated in the present experiments is described elsewhere [18,19]. PP and DAP molecules are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…DAP serves merely as a reference system to provide in comparison with PP information on the degree of pyridyl mediated surface attachment of PP. Substituting four phenoxy groups at the carbocyclic scaffold further on called "bay groups" [18,19] (one of these four groups is marked in Figure 1, left) enhances solvation in toluene (Merck, spectroscopic grade). For ensemble experiments 10 -7 M stock solutions of PBI dye molecules were prepared in toluene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd squares exchange ligands remarkably faster than their Pt analogs. Similar to our results, Wü rthner et al showed that mixing different metallosupramolecular squares, yielded squares that contain statistical amounts of ligands through dynamic ligand-exchange processes [25] . (asterisks indicate small contributions from defects originating from dendron synthesis).…”
Section: Mass Spectrometric Characterization Of Dendritic Assemblies mentioning
confidence: 99%
“…The syntheses of P-PBI, T-PBI, and aT-PBI were reported in previous publications [30,46] and the syntheses of Py-PBI, aPy-PBI, Cl-PBI, and S-PBI followed procedures known from literature [47][48][49]. Experimental details and compound characterizations are given as Supporting Information (SI).…”
mentioning
confidence: 99%